Advancing Radiobiology: Investigating the Effects of Photon, Proton, and Carbon-Ion Irradiation on PANC-1 Cells in 2D and 3D Tumor Models - Alexandra Charalampopoulou; Amelia Barcellini; Giuseppe Magro; Anna Bellini; Sara Sevan Borgna; Giorgia Fulgini; Giovanni Battista Ivaldi; Alessio Mereghetti; Ester Orlandi; Marco Giuseppe Pullia; Simone Savazzi; Paola Tabarelli De Fatis; et al. (Current Oncology, 2025)
Introduction: Pancreatic cancer (PC) is one of the most aggressive and lethal malignancies, calling for enhanced research. Pancreatic ductal adenocarcinoma (PDAC) represents 70–80% of all cases and is known for its resistance to conventional therapies. Carbon-ion radiotherapy (CIRT) has emerged as a promising approach due to its ability to deliver highly localized doses and unique radiobiological properties compared to X-rays. In vitro radiobiology has relied on two-dimensional (2D) cell culture models so far; however, these are not sufficient to replicate the complexity of the in vivo tumor architecture. Three-dimensional (3D) models become a paradigm shift, surpassing the constraints of traditional models by accurately re-creating morphological, histological, and genetic characteristics as well as the interaction of tumour cells with the microenvironment. Materials and Methods: This study investigates the survival of pancreatic cancer cells in both 2D and spheroids, a 3D model, following photon, proton, and carbon-ion irradiation by means of clonogenic, MTT, spheroid growth, and vitality assays. Results: Our results demonstrate that carbon ions are more efficient in reducing cancer cell survival compared to photons and protons. In 2D cultures, carbon-ion irradiation reduced cell survival to approximately 15%, compared to 45% with photons and 30% with protons. In the 3D culture model, spheroid growth was similarly inhibited by carbon-ion irradiation; however, the overall survival rates were higher across all irradiation modalities compared to the 2D cultures. Carbon ions consistently showed the highest efficacy in reducing cell viability in both models. Conclusions: Our research highlights the pivotal role of 3D models in unraveling the complexities of pancreatic cancer radiobiology, offering new avenues for designing more effective and precise treatment protocols.